Why Has the COVID-19 Pandemic Had a Limited Impact on the Primary Housing Market in Poland? - Hanna Augustyniak; Jacek Łaszek; Krzysztof Olszewski; Joanna Waszczuk (Critical Housing Analysis)
In this paper we present the first insights into the as yet unexamined impact of the COVID-19 pandemic on the primary housing market in Poland, with a focus on Warsaw, which is the largest real estate market in the country. We explain the structural features that allowed the market to return to pre-shock levels after the pandemic shock. After the 2007–2008 global financial crisis the negative consequences lasted for several years. This time a sharp monetary policy and fiscal intervention was carried out. Moreover, the developer sector has expanded its production capacity. We show empirically that through monopolistic competition developers were able to restrict the excessive demand that was observed before the COVID-19 pandemic broke out. Another important structural change was the increase in the demand for housing, mainly for investment purposes, which was financed predominantly with cash and contributed to the growth of the rental market.